2018
DOI: 10.1021/acscatal.7b03744
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Asymmetric Cyclopropanation Reaction of Acyclic Amides with Allyl and Polyenyl Carbonates. Experimental and Computational Studies for the Origin of Cyclopropane Formation

Abstract: Cyclopropanes with three chiral centers were afforded in good to high yields with dr ratio of 4−23:1 and ee of 83−99% in the reaction of acyclic amides with monosubstituted allyl carbonates as well as polyenyl carbonates under the Pd-catalysis in the presence of (S phos ,R)-SIOCPhox L1 as the ligand, while allylic alkylated products were provided only if (R phos ,R)-SIOCPhox L2 was the ligand. The amide group of product was easily reduced to hydroxymethyl group in high yield. The active reaction intermediate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…For instance, Hou developed a class of 1,1 ′ -N,P bidentate ligands 1 from Molecules 2024, 29, 968 2 of 17 2001 [23]. The applications of these ligands have demonstrated that the established ligands provide powerful stereo control on the corresponding chiral products in the aggregation of Pd-catalyzed asymmetric reactions [24][25][26]. Alternatively, in 2002, based on the seminal work from Patti's group [27], Moyano and co-workers delivered the absolute configuration of chiral 4-oxazoline ferrocene 2, and then examined the applicability in asymmetric allylic alkylation of rac-(E)-1,3-diphenyl-2-propenyl acetate, which provided the target alkylated product with 97:3 e.r.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hou developed a class of 1,1 ′ -N,P bidentate ligands 1 from Molecules 2024, 29, 968 2 of 17 2001 [23]. The applications of these ligands have demonstrated that the established ligands provide powerful stereo control on the corresponding chiral products in the aggregation of Pd-catalyzed asymmetric reactions [24][25][26]. Alternatively, in 2002, based on the seminal work from Patti's group [27], Moyano and co-workers delivered the absolute configuration of chiral 4-oxazoline ferrocene 2, and then examined the applicability in asymmetric allylic alkylation of rac-(E)-1,3-diphenyl-2-propenyl acetate, which provided the target alkylated product with 97:3 e.r.…”
Section: Introductionmentioning
confidence: 99%
“…Enantiomerically pure cyclopropane derivatives are ubiquitous, nature inspired [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ] building blocks abundantly employed in organic synthesis [ 9 , 10 , 11 , 12 , 13 ], asymmetric catalysis [ 14 , 15 , 16 , 17 ], and medicinal chemistry [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. These advanced synthons are typically accessed via diastereoselective 1,3-ring closure reactions [ 26 , 27 , 28 , 29 , 30 ] or asymmetric cyclopropanation [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. A less established, complementary approach relies on chemo- and diastereoselective installation of additional substituents into pre-formed chiral or prochiral cyclopropanes [ 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetically, the most practical strategy to build the cyclopropane motif consists of an enantioselective cycloaddition between an olefin and a suitable C1 unit 4. For instance, transition-metal catalyzed reactions5 – metal-carbenoid mediated transformations5 a and the ring closure of π-allylpalladium species,5 b Lewis-acid catalyzed Simmons–Smith reactions6 as well as radical processes7 have proven to be powerful methods for the asymmetric cyclopropanations of electron-rich olefins. Complementary, asymmetric Michael-initiated ring-closure (MIRC) reactions have been shown to be an attractive cyclopropanation method for electron-deficient olefins 810.…”
Section: Introductionmentioning
confidence: 99%